Primitive Spatial Graphs and Graph Minors - Ozawa, Makoto; Tsutsumi, Yukihiro (Revista Matemática Complutense, 2007)
Robertson, Seymour, and Thomas characterized linkless embeddings of graphs by flat embeddings, and determined the obstruction set for linkless embeddings. In this paper, we extend flat embeddings to "primitive embeddings" as linkless embeddings to knotless embeddings. Although the obstruction set for knotless embeddings has not been determined, fundamental theorems and conjectures are obtained.